Kesadaran Merek, Citra Merek, dan Asosiasi Merek terhadap Kepuasan Konsumen - Bambang Sutedjo; Yulia Evita Sari (IPM2KPE, 2023)
The purpose of this study was to examine and analyze the influence of brand awareness, brand image and brand associations on customer satisfaction in a case study at Mixue Citra Grand in Semarang City. This research method is quantitative. The sample taken in this study was taken using a purposive sampling technique with the criteria of a consumer who is a student or university student who has purchased and consumed Mixue Ice Cream & Tea Citra Grand in Semarang City. Data were analyzed using validity test, reliability test, multiple regression analysis, F test, determination test (R2), and T test. The results showed, a) brand awareness on consumer satisfaction has a significance value obtained, namely 0.005 <0.05 and the value beta is 0.231 (positive); b) brand image on consumer satisfaction has a significance value obtained, namely 0.00 <0.05 and a beta value of 0.4218 (positive); c) brand association with consumer satisfaction has a significant value obtained, namely 0.001 <0.05 and a beta value of 0.276 (positive). In conclusion, brand awareness, brand image, and brand associations have a positive and significant effect on consumer satisfaction. Keywords: Brand Association, Brand Image, Consumer Satisfaction, Brand Awareness